Returning to study : a guide for professionals - Powell, Stuart (Buckingham : Open University Press, 1999)
Introduction. Thinking and learning. Working and communicating with others. Effective reading and listening. Planning to write. Effective writing. Writing a dissertation or report.
Keywords: Education; Higher education; Continuing education; Adult education; Report writing; Education, Higher -- Great Britain; Adult education -- Great Britain; Continuing education -- Great Britain; Report writing